Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Climate Change and Global Crop Productivity. 2000
DOI: 10.1079/9780851994390.0189
|View full text |Cite
|
Sign up to set email alerts
|

Crop ecosystem responses to climatic change: root and tuberous crops.

Abstract: The responses of root and tuber crops to climatic change are reviewed in this chapter. The topics discussed include: expected effects of climate on root and tuber crops (phenology, development, biomass, yield and photosynthesis); herbivory; and carbon dioxide and climatic change interaction in potato.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…By 2075 only the very wettest areas appear to be able to support a reliable non-irrigated potato crop which indicates that the impact of increased seasonality in precipitation will be very important in the future. Miglietta et al (2000) suggested that there has been too little research into root/tuber crop biology to be sure of the impact of climate change other than to suggest that increased water stress may reduce yields and that elevated CO 2 may increase yields. These general statements clearly apply to the predicted future climate of Ireland and its impact on potato yield.…”
Section: Potatomentioning
confidence: 99%
“…By 2075 only the very wettest areas appear to be able to support a reliable non-irrigated potato crop which indicates that the impact of increased seasonality in precipitation will be very important in the future. Miglietta et al (2000) suggested that there has been too little research into root/tuber crop biology to be sure of the impact of climate change other than to suggest that increased water stress may reduce yields and that elevated CO 2 may increase yields. These general statements clearly apply to the predicted future climate of Ireland and its impact on potato yield.…”
Section: Potatomentioning
confidence: 99%
“…Lobell et al 2008). Two of the suggested adaptation strategies include altering the sowing date and changing variety (Matthews et al 1997), and there are several studies which suggest that either of these strategies might help to mitigate the impact of climate at a local or regional scale (Calvino et al 2003;de Bruin and Pederson, 2008;Andrade, 1995;Fakorede 1985;Challinor et al 2005;Miglietta et al 2000 andMakadho 1996). This paper introduces a methodology for estimating global maize and soybean yield for different levels of global temperature increases.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated minimum temperature (base temperature) for vine elongation rate, leaf addition rate, and leaf area expansion rate were at 16.7, 15.5, and 17.5°C, respectively (Table 2). Leaf production or initiation of leaf primodia is mainly driven by temperature under optimum soil moisture and nutrient conditions (Miglietta et al, 2000). Fujiwara et al (2004) reported that leaf development rate of sweetpotato single node cuttings increased linearly with increasing temperature under artificial light, except at low temperature of 23°C.…”
Section: Resultsmentioning
confidence: 99%
“…According to Indira and Kaberathumma (1988), three important physiological events in the growth phase of sweetpotato are responsible for final crop productivity, namely storage root initiation, storage root development, and storage root maturity. The possible impacts of temperature have not yet been fully comprehended for most species of root and tuber crops (Miglietta et al, 2000) including sweetpotato.…”
mentioning
confidence: 99%